A study of IgG antibodies to the ApoB protein in non-ST segment elevation acute coronary syndrome. (June 2015) - Zhang, Xueying; Yu, Bo; Jin, Yuanzhe; Lei, Mingming; Zhang, Xiaohong; Duan, Zhiying; Lin, Yingzi; Megson, Ian L.; Wei, Jun
Abstract Objectives. It has long been noted that there is an association of antibodies against oxidized low-density lipoprotein (oxLDL) with cardiovascular disease, but the anti-oxLDL antibody has not been confirmed as a biomarker for prediction of acute coronary syndrome (ACS). Apolipoprotein B (ApoB) may carry the epitopes for the immune response to oxLDL. The present work was thus undertaken to detect circulating antibodies to ApoB in non-ST segment elevation ACS (NSTE-ACS). Design. A total of 130 patients with NSTE-ACS and 201 control subjects were recruited. Six ApoB-derived peptipe antigens (Ag1–Ag6) were used to develop an in-house enzyme-linked immunosorbent assay to examine circulating anti-ApoB IgG levels. Results. The anti-Ag1 IgG level was significantly higher in the patient group than the control group (P < 0.001) and the non-ST segment elevation myocardial infarction appeared to be the main form of NSTE-ACS contributing to the increased levels of anti-Ag1 IgG (P < 0.001); there was no significant alteration in the levels of IgG to the other 5 antigens in NSTE-ACS. Conclusions. Circulating anti-ApoB IgG test may be useful for prediction of NSTE-ACS although further confirmation is needed in large-scale clinical studies.